2008
DOI: 10.1016/j.dsr2.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the freshwater balance of northern Marguerite Bay, Antarctic Peninsula: Results from δ18O

Abstract: We investigate the seasonal variability in freshwater inputs to the Marguerite Bay region (Western Antarctic Peninsula) using a time series of oxygen isotopes in seawater from samples collected in the upper mixed layer of the ocean during 2002 and 2003. We find that meteoric water, mostly in the form of glacial ice melt, is the dominant freshwater source, accounting for up to 5% of the near-surface ocean during the austral summer. Sea ice melt accounts for a much smaller percentage, even during the summer (max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 45 publications
3
127
0
1
Order By: Relevance
“…It was found that meteoric water dominated the freshwater budget overall, accounting for up to 5% of the water in the near-surface layer in summer, whereas seasonal variability in sea ice melt was found to be comparable to that of the meteoric water (around 1-2%) (Meredith et al, 2008a). On interannual timescales, variability in the freshwater fractions was found to be significantly influenced by climatic variability associated with both SAM and ENSO (Meredith et al, 2010).…”
Section: Oxygen Isotope Ratios As Oceanographic Tracers At the Wapmentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that meteoric water dominated the freshwater budget overall, accounting for up to 5% of the water in the near-surface layer in summer, whereas seasonal variability in sea ice melt was found to be comparable to that of the meteoric water (around 1-2%) (Meredith et al, 2008a). On interannual timescales, variability in the freshwater fractions was found to be significantly influenced by climatic variability associated with both SAM and ENSO (Meredith et al, 2010).…”
Section: Oxygen Isotope Ratios As Oceanographic Tracers At the Wapmentioning
confidence: 90%
“…At the WAP, we have previously used time series measurements of δ 18 O and salinity from a coastal site in northern Marguerite Bay (close to Rothera Research Station; Figure 1a,b) to document seasonal (Meredith et al, 2008a) and interannual (Meredith et al, 2010) variability in the prevalence of sea ice melt and meteoric water. It was found that meteoric water dominated the freshwater budget overall, accounting for up to 5% of the water in the near-surface layer in summer, whereas seasonal variability in sea ice melt was found to be comparable to that of the meteoric water (around 1-2%) (Meredith et al, 2008a).…”
Section: Oxygen Isotope Ratios As Oceanographic Tracers At the Wapmentioning
confidence: 99%
“…Under equilibrium conditions, freezing produces sea ice with an isotopic signature that is only slightly heavier than the seawater from which it derives, with the fractionation factor being of the order of 1.0026-1.0035 [33,34]. Accordingly, concurrent measurements of δ 18 O and salinity at high latitudes are useful in discerning freshwater inputs of isotopically lighter meteoric sources from isotopically heavier sea-ice melt sources [30,35,36].…”
Section: Data and Methods (A) δ 18 O As A Freshwater Tracermentioning
confidence: 99%
“…The north end of Marguerite Bay is covered by winter sea ice for several months, which provides a useful comparison for seasonal meltwater fluxes from sea ice and glacial sources into the modern James Ross Island area, despite different geographical settings. In Marguerite Bay, between 3 and 5% of the near-surface ocean is estimated as formed by glacial meltwater (Jenkins and Jacobs 2008;Meredith et al 2008), with sea ice-melt accounting for a much smaller percentage (ca. 1%) .…”
Section: Weddell Seamentioning
confidence: 99%
“…1%) . The effects of seasonal sea ice-melt on the 18 O of seawater, and therefore salinity, are minimal ) but those of glacial ice-melt are considerably more significant as high latitude ice has very low 18 O, with values as low as −50‰ (Weiss et al 1979;Meredith et al 2008). The meltwater fraction that we assume for modern waters around James Ross Island may be a little overestimated because here warm water upwelling onto the shelf (Fahrbach et al 1995) is less significant than in Marguerite Bay, which is affected by upwelling of relatively warm Circumpolar Deep Water (CDW) (e.g., Klinck et al 2004).…”
Section: Weddell Seamentioning
confidence: 99%